Crossover-Finite-Size Scaling at First Order Transitions - Borgs, Christian; Imbrie, John Z. (J. Stat. Phys., 1992)
In a recent paper we developed a method which allows to rigorously control the fi nite-size behavior in long cylinders near fi rst-order phase transitions at low temperature